Price Liberalization in a Reforming Socialist Economy : A Search Equilibrium Approach - Fanizza, Domenico (Washington, D.C. : International Monetary Fund, 1992)
A bilateral search model of the commodity market is formulated to study the effects of liberalizing prices in a reforming socialist economy. The main result is that if the competitive structure of the economy is not quickly modified to eliminate supply rents, price liberalization may be accompanied by substantial output losses. A role for tax policy in limiting output losses is identified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Constant Returns To Scale; Lump Sum; Market Economy; Price Liberalization; WP